2019
DOI: 10.1136/bmjpo-2019-000561
|View full text |Cite
|
Sign up to set email alerts
|

Designing and evaluating a novel mobile application for Helping Babies Breathe skills retention in Uganda: comparative study protocol

Abstract: IntroductionOver 600 000 newborns die each year of intrapartum-related events, many of which are preventable in the presence of skilled birth attendants. Helping Babies Breathe (HBB) is a neonatal resuscitation training programme designed for low-resource settings that can reduce both early neonatal mortality and stillbirths. However, as in other similar educational programmes, knowledge and skill retention deteriorate over time. This trend may be counteracted by strategies such as regular simulated exercises.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
7
0
2
Order By: Relevance
“…86 In a 3-year study on HBB program implementation in 15 regions in Tanzania, an assessment of the program's impact on neonatal mortality proved to be challenging because of the poor availability of historical, preintervention data. 25 88 Recent uses of technology to cut costs and ease logistic burden of implementation include training via video conferencing 61 and mobile apps 41 as well as the use of a highfidelity mannequin that provides feedback based on resuscitation performance. 58 HBB implementation translates into meaningfully improved skills and knowledge as demonstrated through multiple studies in which authors cite improved average OSCE scores and pass rates on knowledge assessments.…”
Section: Newborn Outcomesmentioning
confidence: 99%
“…86 In a 3-year study on HBB program implementation in 15 regions in Tanzania, an assessment of the program's impact on neonatal mortality proved to be challenging because of the poor availability of historical, preintervention data. 25 88 Recent uses of technology to cut costs and ease logistic burden of implementation include training via video conferencing 61 and mobile apps 41 as well as the use of a highfidelity mannequin that provides feedback based on resuscitation performance. 58 HBB implementation translates into meaningfully improved skills and knowledge as demonstrated through multiple studies in which authors cite improved average OSCE scores and pass rates on knowledge assessments.…”
Section: Newborn Outcomesmentioning
confidence: 99%
“…This article describes Phase 1, the development of HBB Prompt. More details regarding the entire study can be found in the protocol paper [ 37 ]. Further details including the focus group discussion (FGD) guides for Phase 1 can be found in Additional file 1 and Additional file 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Apps targeted towards newborn health [28][29][30][31][32][33][34] have been created and evaluated previously, some employing UCD, but none have informed their design by exploring the cognitive processes of learning newborn resuscitation skills. Understanding the underlying preferences, perceptions, facilitators and barriers that drive behaviours can help tailor the development of features and functions of apps [25,35,36]. Applying UCD and assessing human factors during the development of a mobile app can enhance user experience and increase the effectiveness of the tool.…”
Section: Introductionmentioning
confidence: 99%
“…102,103 A number of trials are currently underway. 98,104 If shown to be effective, and if adopted and scaled, particularly as integrated interventions, 105 digital tools and platforms may have the potential to address some of the gaps and barriers that have been identified in the dissemination and implementation cascade for HBS. Overcoming these challenges might, in turn, augment global progress toward better policies, outcomes, and clinical care for newborns in LMICs.…”
Section: Lifementioning
confidence: 99%